Lagrange Stability of Semilinear Differential-Algebraic Equations and Application to Nonlinear Electrical Circuits - Filipkovska, M.S. (Журнал математической физики, анализа, геометрии, 2018)
A semilinear differential-algebraic equation (DAE) is studied focusing on the Lagrange stability (instability). The conditions for the existence and uniqueness of global solutions (a solution exists on an infinite interval) of the Cauchy problem, as well as the conditions of the boundedness of the global solutions, are obtained. Furthermore, the obtained conditions of the Lagrange stability of the semilinear DAE guarantee that every its solution is global and bounded and, in contrast to the theorems on the Lyapunov stability, allow us to prove the existence and uniqueness of global solutions regardless of the presence and the number of equilibrium points. We also obtain the conditions for the existence and uniqueness of solutions with a finite escape time (a solution exists on a finite interval and is unbounded, i.e., is Lagrange unstable) for the Cauchy problem. The constraints of the type of global Lipschitz condition are not used which allows to apply efficiently the work results for solving practical problems. The mathematical model of a radio engineering filter with nonlinear elements is studied as an application. The numerical analysis of the model verifies theoretical studies Проводиться дослiдження напiвлiнiйного диференцiально-алгебраїчного рiвняння (ДАР) з акцентом на стiйкiсть (нестiйкiсть) за Лагранжем. Отримано умови iснування та єдиностi глобальних розв язкiв (розв язок iснує на нескiнченному iнтервалi) задачi Кошi, а також умови обмеженостi глобальних розв язкiв. Бiльш того, отриманi умови стiйкостi за Лагранжем напiвлiнiйного ДАР гарантують, що кожний його розв'язок є глобальним i обмеженим, та, на вiдмiну вiд теорем про стiйкiсть за Ляпуновим, дозволяють довести iснування та єдинiсть глобальних розв язкiв незалежно вiд наявностi та кiлькостi точок рiвноваги. Також отримано умови iснування та єдиностi розв язкiв зi скiнченним часом визначення (розв'язок iснує на скiнченному iнтервалi та є необмеженим, тобто нестiйким за Лагранжем) для задачi Кошi. Не використовуються обмеження типу глобально умови Лiпшиця, що дозволяє ефективно використовувати результати роботи у практичних застосуваннях. В якостi застосування дослiджено математичну модель радiотехнiчного фiльтру з нелiнiйними елементами. Чисельний аналiз моделi пiдтверджує результати теоретичних дослiджень.